Extension comes to life again - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Training for Agricultural Development 1997-1998. FAO. 1998. 178 pp. ISBN 92 5 104182 2.$28.00, e 26.90 See FAO reference elsewhere in this section for address.